The Effect of Corporate Digitalization on the Value of Firm - Santosa, Yolanda Elin; Salma, Dini Kamilia (Universitas Hayam Wuruk Perbanas, 2022)
Information digitalization provides convenience for various parties. In the business world, companies provide digital information to investors for creating signals of development or growth in their business. In this study, the researchers seek to determine the effect of digitizing information on firm value. This quantitative research method uses a sample of all companies listed on the IDX in 2020. The results show that information digitalization does not affect the firm value. Based on this evidence, it implies that this research can provide provide insight for the company. This can be due to the consideration of the large number of internet users, in which the companies can provide company information such as company performance, and general notifications regarding the company through other media such as social media.